Consciência linguística: reflexões na sala de aula sobre usos do português brasileiro - Fabiana Gomes Cortes Mol (2023)
Linguistic events occur naturally anywhere and everywhere, and school is the best place to learn to practice and clearly assess particular aspects of each linguistic event, having as a principle the effective use of language as an inherent right of each person. However, mistakes have been made around teaching practices, which occur in various facets of the school. In the field of language, there is still the unfortunate reproduction of the discourse that leads the school community to believe that only the holders of the standard language variety are worthy of credibility, to the detriment of peripheral languages, which would represent a “shame for its speakers”, according to such discourse. Thus, the school further marginalizes certain groups, when its function should be to empower minority groups. With a view to changing this panorama, this work contribute to students' critical linguistic awareness, through reflective analyzes in the classroom about the diversity of uses of the Portuguese language. The analysis of posts and comments, videos and news, present in social networks, which evidence and question the reproduction of the myth of the perfect language, contribute to this awareness, based on the studies of Bagno (2000; 2005), Faraco (2002; 2017), Kleiman (2010), Nascimento (2019), Travaglia (2009), Veronelli (2021) and other authors. As for the research,called Intervention Research, the approach is of a qualitative nature and confirms the didactic relevance of the proposed activities.